A systematic review of economic evaluation studies of health technologies in the Philippines - Albania, Mattew P.; Defensor, Cyro Angelo; Largo, Brainy Luv A.
Introduction: The Universal Healthcare Act established health technology assessment as a transparent, evidence-based tool to guide the Department of Health and PhilHealth in setting priorities. In 2020, a guidance document was released to standardize the conduct of assessments, including economic evaluations. However, there remains no synthesized evidence on the status of economic evaluation studies of health technologies in the Philippines following its dissemination.